Motivations Associated with Food Choices and Eating Practices - Guiné, Raquel P. F. (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book is generally focused on food choice and which factors are associated with the decisions that define people's eating behaviour. These factor are highly variable and include influences from the surrounding environment as well as the individual characteristics of each person. The book includes a number of chapters that address these issues from different points of view. Some explore the psychology of food choices or the cultural aspects and tradition, as well as the influence of surrounding contexts. Others focus on the role of lifestyle on eating practices and health motivations, but also the food marketing and the sensory aspects of food, as a way to incentive consumption. Finally, sustainability concerns and environmental impacts can also shape and help change people's food choices.Within the chapters gathered on this book you will find key topics that apply to everyday food choices or that can help target food consumption goals towards better health, more sustainable food chains and happier life styles.